Implementing a Differentiation Approach in Teaching to Accommodate Diverse Learning Styles of Primary School Students : A Systematic Literature Review - Putri, Kharisma; Elizar (Universitas Pendidikan Ganesha, 2025)
The differentiated learning approach is able to accommodate the diverse learning needs and preferences of students in order to improve learning outcomes and critical thinking skills. This study aims to explore the implementation of differentiation through the adjustment of learning content, processes, and products based on visual, auditory, and kinesthetic learning styles. This research uses the Systematic Literature Review (SLR) method with the subject being relevant literature, collected through Google Scholar and classroom observation. The data were analyzed through five stages of systematic literature selection. In the initial stage, 90,600 documents related to “differentiation” were found. Selection by publication year (2019-2023) reduced the number of documents to 18,000. The addition of the keyword “learning style” narrowed down the documents to 1,820. The next stage used the additional keyword “elementary school students,” resulting in 259 documents. In the final stage, the data was further filtered until 9 documents remained which were analyzed in depth. This study found three main points related to the effectiveness of differentiated learning. First, the implementation of differentiation significantly improved students' collaboration skills and academic results. Second, the success of implementation was influenced by variations in visual, auditory, and kinesthetic learning styles, so teaching strategies needed to be adapted to the dominant style in the classroom. Third, differentiation has a positive impact on critical thinking skills, surpassing the results of traditional methods. These findings confirm that differentiated instruction creates an inclusive and adaptive learning environment to meet the diverse needs of students.